INOVASI PEMBANGUNAN INKLUSIF PEMERINTAH KOTA CIREBON PADA PROGRAM PERLUASAN AKSES DAN KESEMPATAN BELAJAR DI ERA PANDEMI COVID-19 - Dea Angkasa Putri Supardi (SOSFILKOM : Jurnal Sosial, Filsafat dan Komunikasi, 2025)
The COVID-19 pandemic created multidimensional challenges for development, particularly in the education sector, where learning activities were disrupted by social restrictions. This situation required local governments to introduce innovative policies to ensure inclusive and sustainable educational services. This article aims to describe the inclusive development innovation implemented by the Cirebon City Government in expanding access to learning opportunities for primary school students during the COVID-19 pandemic. The discussion adopts a descriptive approach by reviewing government policies, inclusive development indicators, and educational program implementation throughout the pandemic. The findings indicate that the Cirebon City Government successfully implemented a pentahelix collaboration involving government institutions, the private sector, communities, media, and academia. This collaborative approach was realized through the implementation of distance learning, the development of e-learning platforms, the provision of internet data assistance, the utilization of digital media and local television for educational delivery, and the strengthening of parental and school committee involvement in supporting students' learning activities. The synergy among stakeholders enabled the continuity of educational services while expanding learning access during the pandemic. These findings suggest that the pentahelix collaboration model represents an effective strategy for promoting inclusive development, particularly in the education sector during times of crisis.